PENGARUH TAYANGAN SINETRON ANAK LANGIT SCTV TERHADAP PERILAKU AGRESIF PADA REMAJA (SURVEI TERHADAP SISWA-SISWI MTS MANARATUL ISLAM JAKARTA) - Santika Oktavian; Fatmawati Fatmawati (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2018)
This research uses positivism paradigm, with quantitative approach, this research method type is survey. Sampling technique used is Purposive Sampling with 65 respondents. While the type of data used is the primary data obtained from the questionnaire to the students of MTS Manaratul Islam Jakarta seventh and eighth grade and the method of data analysis used is Linear Regression. The theory used is Social Bandura.In the four processes of social learning proposed by Albert Bandura, the Attention Process of 50.77% -55.38% of the students observed scenes that display aggressive behavior on the show of soap operas of the Sky Children. In Retention Process of 30.77% -38.46% of students remember scenes that display aggressive behavior on the show. In Motoris Reproduction Process6,15% -18,46% the students mimic aggressive behavior that aired on the show. Then, the Motivational Process of 10.77% of students were satisfied after imitating aggressive behavior on the show. The cognitive condition of the students states that the content of the message in the soap opera of Anak Langit is about fighting between motorcycle gangs. The affective condition of the students is interested in watching the show because of the beautiful and handsome appearance of the players, and according to those scenes that show aggressive behavior in soap operas is a behavior or behavior that is not worthy of being imitated, and watching the soap opera of Anak Langit is a demands in the association. small students mimick aggressive behavior on the show. Keywords: Influence, Impressions, Sinetron, Behavior, and Aggressive